2021
DOI: 10.1038/s41440-021-00760-9
|View full text |Cite
|
Sign up to set email alerts
|

A Japan nationwide web-based survey of patient preference for renal denervation for hypertension treatment

Abstract: Renal denervation is a potential alternative to antihypertensive drug therapy. However, data on patient preference for this treatment option are limited and there are no data specifically from Asian patients. This study evaluated patient preference for renal denervation in patients with hypertension from Japan. Patients were a subset of those who participated in a March 2020 online electronic survey of patients with hypertension who had regularly visited medical institutions for treatment, were receiving antih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In a countrywide survey of Japanese patients, the Kario et al 2022 study looked into patients’ preferences for renal denervation. 21 The study discovered that nearly one-third of the patients preferred RDN, among which patients with resistant hypertension, poor adherence to antihypertensive medications, younger patients, and patients with side effects during antihypertensive treatment were more likely to prefer RDN. 21 A similar study conducted in Germany 22 revealed that RDN was favored by 38.2% of individuals who were not already taking medicine and by 28.2% of those who were.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a countrywide survey of Japanese patients, the Kario et al 2022 study looked into patients’ preferences for renal denervation. 21 The study discovered that nearly one-third of the patients preferred RDN, among which patients with resistant hypertension, poor adherence to antihypertensive medications, younger patients, and patients with side effects during antihypertensive treatment were more likely to prefer RDN. 21 A similar study conducted in Germany 22 revealed that RDN was favored by 38.2% of individuals who were not already taking medicine and by 28.2% of those who were.…”
Section: Resultsmentioning
confidence: 99%
“… 21 The study discovered that nearly one-third of the patients preferred RDN, among which patients with resistant hypertension, poor adherence to antihypertensive medications, younger patients, and patients with side effects during antihypertensive treatment were more likely to prefer RDN. 21 A similar study conducted in Germany 22 revealed that RDN was favored by 38.2% of individuals who were not already taking medicine and by 28.2% of those who were. Patients’ preferences were found to be influenced by antihypertensive effects, the experience of side effects, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneous BP responses after RDN were mainly from appropriate patient selection. Patient preference should also be part of the decision-making in patient selection [ 11 ]. The ideal candidates for RDN are patients with autonomic hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these plant metabolites aid in the reduction of oxidative stress, making them potentially useful in the treatment of a wide range of severe illnesses. Despite the availability of numerous medications to treat oxidative stress-related chronic diseases, the high profile of drug side effects necessitates the use of alternative and complementary treatment options for diabetes and cardiovascular diseases (CVDs), such as coronary artery disease (CAD) and blood pressure control [ 2 , 3 ]. To avoid or treat chronic disorders, lifestyle adjustments and dietary interventions, such as increasing fruit and vegetable consumption, are frequently advocated [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%